Are Self-Efficacious Individuals more Sensitive to Organizational Justice Issues? The Influence of Self-Efficacy on the Relationship between Justice Perceptions and Turnover - AŞKUN, OLCAY BİGE (WILEY PERIODICALS, INC, 2018)
Moderating role of self-efficacy has been studied in several research contexts which also frequently involved organizations. According to the theoretical framework borrowed by social cognitive theory and referent cognitions theory, we have decided to explore the moderating role of self-efficacy in the relationship between justice perceptions and turnover intentions. Nine-hundred and four employees coming from private companies in Istanbul and Ankara participated in our study. Our results revealed important findings in relation to the moderating effects of different self-efficacy dimensions. Many interaction effects were as expected, except for those high in willingness to expend effort in completing the behavior. We discussed the results in light of certain theoretical assumptions and offered related recommendations for organizational practice and future research.
Keywords: self-efficacy; social cognitive theory; referent cognitions theory; perceptions of justice; turnover intentions; SOCIAL-COGNITIVE THEORY; DISTRIBUTIVE JUSTICE; PROCEDURAL JUSTICE; JOB-SATISFACTION; MODERATING ROLE; PERFORMANCE; INTENTIONS; PAY; CITIZENSHIP; COMMITMENT